76.6k views
0 votes
Someone answer this I’ll give you all my points

Someone answer this I’ll give you all my points-example-1
User Macy Abbey
by
6.5k points

1 Answer

4 votes

Answer:

Equation; y = - x + 3

Explanation:

To determine the equation, let us first determine the slope of the line, through the equation ( y2 - y1 ) / ( x2 - x1 ), in this case where y2 ⇒ 1, y1 ⇒ 5, x2 ⇒ 2, and x1 ⇒ -2;

( 1 - 5 ) / ( 2 - ( - 2 ) ) ⇒ Simplify,

( - 4 ) / ( 4 ),

Slope; - 1

Now that we have the slope, let us substitute this known value into the point - slope equation in the following form;

y = a * x + b, where a ⇒ slope, and b ⇒ y - intercept,

( So far we have ) y = - x + b,

Let us solve for the value of b in y = - x + b by substituting one of the points, say ( 2 , 1 ) where x ⇒ 2, and y ⇒ 1;

( 1 ) = - ( 2 ) + b,

1 = - 2 + b,

b = 3;

Equation; y = - x + 3

User Chika
by
6.2k points